Assessment of drug related problems and clinical pharmacist interventions in paediatric department of a tertiary care teaching hospital - Pemmasani, Deepishka; Gali, Sai Deepak; Arcot, Maanasa; T. S., Durga Prasad (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug-related problems (DRPs) are frequent in hospitalization in pediatrics. The main aim of present investigation is to assess drug related problems and clinical pharmacist interventions in pediatric department of tertiary care hospital. Methods: It was a prospective, observational and interventional study carried over a period of 6 months. Results: A total of 66 patients were identified with drug related problems. Among them 31 (42%) were in between 1month–2 years followed by 25 (34%) were in between 2-11 years, 10(24%) were in between 11-18 years of age. 30(45.3%) patients were prescribed with 0-3 drugs followed by 21 (31.3%) were prescribed with 3-5 drugs, 15(23.3%) were prescribed with 6-10 drugs. Most of the DRP’s observed in the study were drug interactions 52(78.78%) [major-19 (36.53%), moderate-27 (5192%) and minor-6(11.53%)] followed by adverse drug reactions 12 (18.18%), and duplication errors were 2 (3.03%). Majority of the clinical pharmacist recommendations were duration change 52 (34.66%), drug change 10(6.66%), dose reduction 2 (1.35%) followed by drug termination 2 (1.33%). Major significance of DRPs were noted high 31(57.96%), whereas 25 (39.8%) were moderate and 8 (12.12%) were minor. The acceptance rate of intervening clinical pharmacist recommendation and change in drug therapy was found to be high in 57 (86.66%) cases while in 9 (13.33%) cases suggestions were accepted but therapy was not changed. There were no cases with neither suggestion were accepted nor therapy changed. Conclusions: Clinical pharmacist involvement in inpatient pediatric care can significantly help to identify, resolve and prevent the drug related problems. The study concluded that the clinical pharmacist has a significant role in patients care at hospital.